2002
DOI: 10.1094/phyto.2002.92.5.542
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Citrus Viroids in Citrus from Japan and Their Ability to Produce Exocortis-Like Symptoms in Citron

Abstract: Sequential polyacrylamide gel electrophoresis analyses showed many viroid-like RNAs in samples collected from citrus trees in Japan. Reverse transcription polymerase chain reaction and sequencing analyses of the amplified fragments verified that they were derived from variants of six citrus viroids, Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd) including CVd-I-LSS (a distinct variant of CBLVd), Hop stunt viroid, Citrus viroid III, Citrus viroid IV, and Citrus viroid OS. The samples induced sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 27 publications
4
47
0
8
Order By: Relevance
“…The RT-PCR technique is the most commonly used alternative for detecting viruses and viroids that affect citrus (Yang et al, 1992). Various publications have proposed a multiple RT-PCR method for detecting the major citrus viroids in a single reaction (with reverse transcription and amplification within the same tube), which have given satisfactory results in decreasing plant contamination, work-time and cost (Yang et al, 1992;Ito et al, 2002a;Bernard and Durán-Vila, 2006). Other authors have proposed detection using multiple RT-PCR only for viruses that affect Prunus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The RT-PCR technique is the most commonly used alternative for detecting viruses and viroids that affect citrus (Yang et al, 1992). Various publications have proposed a multiple RT-PCR method for detecting the major citrus viroids in a single reaction (with reverse transcription and amplification within the same tube), which have given satisfactory results in decreasing plant contamination, work-time and cost (Yang et al, 1992;Ito et al, 2002a;Bernard and Durán-Vila, 2006). Other authors have proposed detection using multiple RT-PCR only for viruses that affect Prunus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low sequence identity (94.3%) was consequence of 13 changes, two deletions and an addition that affected the upper and lower strands of the regions flanking the Central Conserved Region (CCR), and affecting the HSVd secondary structure. This variant had a high identity (99.7%) with a cachexia inducing variant previously described in Japan (Ito et al, 2002).…”
Section: Introductionmentioning
confidence: 60%
“…Se han establecido distintas aproximaciones, protocolos e incluso combinaciones de cebadores que permiten la detección de todos los viroides mediante un sistema de multiplex RT-PCR (Ito et al, 2002). A pesar de las ventajas de este método, la detección rutinaria mediante RT-PCR como metodología única en programas de certificación no ha llegado a generalizarse (Sieburth et al, 2002), ya que con cierta frecuencia se obtienen falsos negativos en muestras que se sabe que están infectadas, así como amplificaciones inespecíficas que dificultan la interpretación de los resultados obtenidos (Garnsey et al, 2002).…”
Section: Métodos De Diagnóstico Y Detección De Los Viroides De Los Cíunclassified
“…Se considera un viroide quimérico pues presenta una similitud de secuencia con CDVd y ADFVd en los dominios C y T L , y con CEVd en los dominios V y T L . Este viroide se ha detectado en variedades de naranjo dulce,reticulata) únicamente en Japón (Ito et al, 2002). En cidro Etrog causa necrosis suave en el pecíolo y doblamiento de las hojas.…”
unclassified
“…Attempts to use electrophoresis or molecular hybridization analysis resulted in unreliable results because in many citrus species and cultivars, viroids do not accumulate at high enough titers to be detected . However, since all citrus viroids do accumulate at detectable titers in Etrog citron, this species has been used as a secondary bio-amplification host, which, when coupled with molecular analysis, is a very sensitive and specific procedure for indexing purposes Duran-Vila et al, 1993).More recently and because of its great sensitivity, RT-PCR is considered as a desirable alternative to other diagnostic methods and many protocols have been proposed (Yang et al, 1992; Nakajara et al, 1999;Ito et al, 2002;Ragozzino et al, 2004; Reanwarakorn and Semancik, 1999; Tessitori et al, 2004). Unfortunately, the experience accumulated over the years has shown that false positives due to amplicon contamination and false negatives due to the failure to generate a cDNA of suitable size during reverse transcription are not infrequent (Bernad and Duran-Vila, 2006).…”
mentioning
confidence: 99%